Art et nation : la Commémoration de Haendel en 1784 ou l’institution d’un rituel patriotique - Pierre Dubois (Revue Française de Civilisation Britannique)
The great Handel Commemoration in Westminster in 1784 was a watershed in British cultural history and quite clearly questions the relation between art and nation.Organised as a real political project, it was that unique moment when music was suddenly invested with a strong ideological and political significance. The Commemoration contributed to the construction of a true “Handelian mythology” that had strong patriotic overtones. Handel’s music was regarded as sacred and consequently ritualised, while the Commemoration aimed at spectacularly instituting national music. Through a kind of analogy, the conservative social elites intended to express their commitment to the principle whereby the “institutions” – whether musical or political – were to remain immutable.